Exploring regional dynamics in Sub-Saharan African agriculture - Diao, Xinshen; Yanoma, Yukitsugu (International Food Policy Research Institute, 2003)
Identifying growth poles in the SSA region, strengthening linkages and generating mutual benefits across African countries is an important part of the strategy to promote agriculture-led growth at the Africa-wide scale. Using agricultural trade data, this study focuses on identifying major countries that play important roles in regional agricultural trade and commodities in which African countries have a comparative advantage and where there is potential for more trade within the region....Poor infrastructure and institutional barriers are among the major reasons constraining African countries to exploit their comparative advantage and strengthen their economic linkages. The model simulations show that opening the EU market is strongly in the common interest of African countries. Reducing African countries own trade barriers, both in agriculture and non-agriculture, can significantly increase intra-regional agricultural trade. However, the benefit of the globalization and agricultural trade liberalization to the African countries would be limited by poor market access conditions such as transportation and other infrastructure. Because of these, many African agricultural commodities can hardly reach domestic and regional markets, or be exported to the world. Without improving the efficiency of these nonagricultural sectors that provide critical inputs or services to agricultural production and trade, it is virtually impossible for the countries of SSA to increase their competitiveness in international markets. -- from Authors' Abstract